The Potential Of Wave And Offshore Wind Energy In Around The Coastline Of Malaysia That.Face The South China Sea. - Chiang, E.P.; Zainal, Z. A.; Narayana, P. A, Aswatha; Seetharamu, K. N. (2003)

(untitled)
The world wide estimated wave energy resource is more than 2 TW. Offshore wind speeds are generally higher than wind speeds over land, hence higher available energy resource. The estimated offshore wind potential in European waters alone is in excess of2500 TWh/annum. Offshore area also provides larger area for deploying wind energy devices. In recent year efforts to promote these two types of renewable and green energy sources have been intensify. Using the data obtained from the Malaysia Meteorological Service (MMS) analysis was conducted for the potential of wave energy and wind energy along the coastline of Malaysia facing the South China Sea. Maps of wave power potential were produced. The mean vector wind speed and direction were tabulated.